Cancer Progression : Focus on Platelet - Erty Sundarita; Mediarty (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2021)
Platelets are an important component in the process of hemostasis and coagulation. It’snow known that high platelets count closely related to poor prognosis of patients withcancer, due to their role in the hematogenous spread of cancer cells. Platelet can beactivated by cancer cells into tumor educated platelet and then cause thrombosis throughtumor induced platelet aggregation. Platelet also protect cancer cells in the blood circulationfrom natural killer cells and help the transition of cancer cells from epithelial tomesenchymal and vice versa, resulting in the process of metastasis. In the next stage ofmetastasis, platelets trigger extravasation of cancer cells from primary cancer and helpadhesion of cancer cells to distant organs.